Low temperature modifies seedling leaf anatomy and gene expression in Hypericum perforatum - Su, Hongyan; Jin, Ling; Li, Mengfei; Paré, Paul W. (Frontiers in Plant Science, 2022)
Hypericum perforatum, commonly known as St John's wort, is a herbaceous perennial that produces the anti-depression compounds hypericin (Hyp) and hyperforin. While cool temperatures increase plant growth, Hyp accumulation as well as changes transcript profiles, alterations in leaf structure and gene expression specifically related to Hyp biosynthesis are still unresolved. Here, leaf micro- and ultra-structure is examined, and candidate genes encoding for photosynthesis, energy metabolism and Hyp biosynthesis are reported based on transcriptomic data collected from H. perforatum seedlings grown at 15 and 22°C. Plants grown at a cooler temperature exhibited changes in macro- and micro-leaf anatomy including thicker leaves, an increased number of secretory cell, chloroplasts, mitochondria, starch grains, thylakoid grana, osmiophilic granules and hemispherical droplets. Moreover, genes encoding for photosynthesis (64-) and energy (35-) as well as Hyp biosynthesis (29-genes) were differentially regulated with an altered growing temperature. The anatomical changes and genes expression are consistent with the plant’s ability to accumulate enhanced Hyp levels at low temperatures.